The Concept of Mut'ah Marriage in Islamic Jurisprudence - Afiful Huda (VRISPRAAK : International Journal of Law, 2024)
Nikah Mut'ah contract is when a man marries a woman by specifying the length of their marriage period, whether it is a day, a week, or a month, or other time limits. That mut'ah marriage was once allowed by the Prophet PBUH is not denied by Ahlu Sunnah scholars. There are reports that mention the practice of mut'ah marriage at the time of the Prophet, but there are also many reports that confirm that mut'ah marriage has been cancelled. The schools of Maliki, Shafi'I, Hanafi and Hambali agree that mut'ah marriage or contract marriage is haram and invalid. Imam Shafi'i said, Mut'ah marriage which is prohibited is all marriages that are limited by time, either in the short term or long term, while Imam Nawawi said, Mut'ah marriage is not allowed, because marriage is basically a mutlaq aqad, so it is not valid if it is limited by time.